Multimedia in journalism - Kišiček, Sanja (2008)
Flash is a powerful tool. The engines of new technologies and different forms for content presentation set a great challenge to multimedia news designers. Incorporating text, sound, picture and animation in a news slideshow creates an illusion of reality making the news more actual, the event more significant, and the audience more informed. Depending on the goals of news presentation, a designer includes appropriate modules and media. The main goal is to affect, to leave an impact by engaging as more human senses as possible, meaning that for e.g. the scene in the photo might show something that cannot be adequately described with words. Furthermore, sound adds a dimension that photos with text captions do not, and cannot possess, i.e. sound adds information for the audience to experience the photo. From the psychological point of view, humans perceive data step by step, having the cognitive capabilities limited. Therefore, one of the greatest advantages of multimedia news is the interactivity of such a presentation – a user possesses the sense of power and control by always being able to stop, rewind or replay.